Effect of seepage velocity on the attachment efficiency of TiO2 nanoparticles in porous media - Kim, Changwoo; Lee, Seunghak (ELSEVIER SCIENCE BV, 2014)
Previously identified relationships between the attachment efficiency (alpha) and seepage velocity (U-S) of nanoparticles (NPs) were tested under simulated subsurface transport conditions, where the value of Us is typically much less than the Us on which they are based. This found an increase in the alpha value of TiO2 NPs with respect to Us, which contradicts previous reports suggesting a constant value or decrease. By comparing the adhesion energy of the TiO2 NPs to sand and the hydrodynamic energy required to detach them, the increase of alpha with respect to U-S is found to be due to the difference in the magnitude of U-S considered; with 6.1E-05 to 1.3E-03 ms(-1) used in previous studies, whereas the current study uses a value in the range from 2.4E-06 to 4.9E-04m s(-1). Only one of the previous models predicting alpha showed a similar increase of alpha with U-S, which was the result of it employing low velocities to examine the effects of organic matter. The current findings therefore suggest that previously determined relationships between alpha and U-S need to be further developed to incorporate more variables before they can be effectively used to describe or predict the subsurface transport of TiO2 NPs. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: UNFAVORABLE SURFACE INTERACTIONS; MANUFACTURED NANOPARTICLES; COLLOID DEPOSITION; TRANSPORT; PARTICLES; FILTRATION; AGGREGATION; DETACHMENT; REMOVAL; HYDRODYNAMICS